Pengaruh Penggunaan Media Website Terhadap Sikap Remaja Dalam Mengkonsumsi Tablet Tambah Darah di Sman 1 Wanaraya Wilayah Kerja Puskesmas Wanaraya Tahun 2025 - Saprina _ Herdayanti; Rita Kirana; Suhrawardi -; Nur Rohmah Prihatanti (JURNAL KEBIDANAN BESTARI, 2026)
Abstract Iron deficiency anemia is a major health problem among adolescent girls. At SMAN 1 Wanaraya, compliance with Iron Supplement Tablets (TTD) consumption is still low. An attractive and easily accessible educational medium such as a website is needed to increase positive attitudes towards TTD consumption. This study was conducted to analyze the effect of website use on adolescent attitudes towards iron supplement tablet consumption at SMAN 1 Wanaraya. This quasi-experimental study used a one-group pre-test-post-test design. A sample of 71 female students was selected using systematic stratified sampling. Data were collected using attitude questionnaires before and one week after accessing the educational website “RematriDarah.SH”. Analysis was performed using the Wilcoxon Signed Rank Test non-parametric statistical test. The results showed an increase in the average attitude score of adolescents from 27.51 (pre-test) to 29.86 (post-test). Statistical tests showed a significant difference (Z = -6.969; p = 0.000), proving that the website media had a significant effect on increasing the attitude scores of adolescents. Based on the research results obtained, educational websites were proven to significantly increase the positive attitudes of female adolescents towards the consumption of iron tablets at SMAN 1 Wanaraya. It is recommended that health and education institutions consider the use of websites as one of the strategies for adolescent health education. Keyword: Website Media, Attitude, Adolescent Girls, Iron Supplement Tablets